Aplikasi Buku Tamu Menggunakan Qr Code Berbasis Web Pada Layanan Pengadaan Secara Elektronik (LPSE) Provinsi Jambi - Muhammad Depryansyah S; Umi Kalsum; Rahmayani Harahap; Zikri Ariyanto; Lala Pita; Stefany Putri Astari; Utami Mizani Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
The use of Electronic Procurement Services (LPSE) in Jambi Province has become one of the main approaches in increasing transparency and efficiency in the government procurement process for goods and services. However, security and accountability issues remain the main focus in the development of this system. This research aims to develop and evaluate a QR Code-based guestbook application that is integrated with the Jambi Province LPSE system. This system development method uses a qualitative and quantitative approach. Literature studies are used to design applications that meet the security and functionality requirements of LPSE. The development was carried out by utilizing web technology and QR Code to facilitate recording the attendance of LPSE users effectively and efficiently. Application evaluation was carried out through trials with the participation of Jambi Province LPSE users. Data collected includes system reliability, user responsiveness, and ease of integration with existing systems. The evaluation results are used to improve and optimize the application to meet security standards and LPSE user needs. It is hoped that the results of this research can make a positive contribution in improving attendance management and transparency in LPSE Jambi Province through the implementation of innovative QR Code technology.